CULTURAL HETEROGENIZATION IN RAJA AMPAT TRADITIONAL SOCIETY (Case study on modernity power in Waisai regency of Raja Ampat, West Papua) - George Mentansan (Universitas Padjadjaran, 2022)
Indigenous peoples are groups of people who live with traditional values and norms as guidelines in their daily life. The system of tools and equipment for life is still simple, kinship is still very close, religion and art form a complete unity in building harmony with nature, It turns out that being faced with a phenomenon of modernity that was born as a conqueror with its supporting tools such as the capitalist economy, industrialization, exploitation of natural resources, supervision of the dominant group, rationalization of values and secularization have moved quickly to attack and dominate the Raja Ampat indigenous peoples. This study aimed to explore the conditions, forms and impacts of modernity power in the Raja Ampat traditional community. Furthermore, the research employed a qualitative case study method with an ethnographic approach in Waisai, Raja Ampat Regency. The technique of determining informants was carried out purposively by collecting primary data and secondary data. The research data collected were analyzed using data reduction techniques, data presentation and drawing conclusions. The data presentation was done in a descriptive qualitative manner with scientific variety language. The results show cultural heterogenization forms including an existing capitalist economy with several employment opportunities, industrialization in fisheries and tourism, massive natural resource exploitation, supervision of dominant groups like the Raja Ampat bureaucracy, values rationalization and secularism without territorial and customary boundaries. However, this is also problematic because the products of modernity mediate life demands to move quickly, precisely, effectively and efficiently.